European experience of organizational and legal provision of sustainable spatial development (Economics and region, 2023)
The article analyses the European experience of organisational and legal support for sustainable spatial development of territories. The study includes an analysis of the legislation, regulatory framework and strategic documents governing the processes of sustainable spatial development of the territories of Ukraine and the European Union. The paper analyses the most effective tools and practices used in Europe to ensure sustainable development at different territorial levels: local, regional and national. The main characteristics of the Polish Concept of National Spatial Development until 2030 are investigated, where the modern approach is based on breaking the existing dichotomy of spatial and socio-economic planning at the national, voivodeship, local level in relation to functional areas. Using the results of the ESPON COMPASS project 2016-2018, the role of the European Union in shaping: national territorial management and spatial planning; the main common features and differences that characterise the Europeanisation of territorial, spatial management and planning, as well as the study of actual potential and exchange of experience; integration policy and cohesion policy, and the involvement of citizens in the organisation of spatial development of territories is investigated. The article focuses on four dimensions of sustainable development: economic, environmental, social, and cultural sustainability. The directions and mechanisms of interconnection of spatial and socio-economic planning, implementation of integrated spatial development at the national, regional and local levels are outlined. The main roles of state and public institutions in the organisation of sustainable spatial development of territories are defined. The article summarises the conclusions on the European experience of ensuring sustainable spatial development and emphasises the importance of taking into account unique national and regional characteristics in the formation and implementation of sustainable development strategies.
Keywords: sustainable spatial development; European integration; organizational and legal foundations; region; state; functional territories